PENGELOLAAN KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI KEWIRAUSAHAAN MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Indah Surya Wardani Indah Surya Wardani (Manajer Pendididikan, 2015)
This study aims to determine management the problem solving and enterpreneurship  communication students. Popolation in this study were all students of class XII of TP SMK N 2 Bengkulu City. This research is experimental and instrument used is the type of the test (about problem solving and communication) and non-test (student attitude scale). Collecting data using test instruments. The results showed that an increase in problem-solving and communication abilities of students receiving enterpreneurship cooperative learning jigsaw better than students who received conventional learning.Keywords: enterpreneurship, problem solving, learning, jigsaw, cooperative.